Iron Deposition Leads to Neuronal α-Synuclein Pathology by Inducing Autophagy Dysfunction - Wan, Wenbin; Jin, Lirong; Wang, Zigao; Wang, Lingyan; Fei, Guoqiang; Ye, Fanlong; Pan, Xiaoli; Wang, Changpeng; Zhong, Chunjiu (Frontiers in Neurology, 2017)
Abstract Growing evidence has indicated that iron deposition in the substantia nigra (SN) plays an important role in Parkinson’s disease (PD). However, the underlying mechanism is still elusive. Using primary dopaminergic neurons and SH-SY5Y cells cultured in vitro, we observed that iron loading increased α-synuclein and reactive oxygen species (ROS) levels in these cells but did not affect the intracellular α-synuclein mRNA levels. Furthermore, iron loading significantly downregulated Beclin-1 levels and decreased the ratio of microtubule-associated protein 1 light chain 3 isoforms (LC3 II/LC3 I). However, a significant change in the levels of autophagy-related gene 5 (Atg5) was not observed in either neurons or SH-SY5Y cells after iron treatment. After treatment with rapamycin, the iron loading-induced increase in the α-synuclein level was significantly reversed and ROS generation was alleviated in both cultured neurons and SH-SY5Y cells. These results indicate that the inhibition of autophagy is critical for the pathological alterations in α-synuclein induced by iron loading. Moreover, treatment with vitamin E did not affect the increase in the α-synuclein levels but significantly eliminated the iron-induced ROS production. Together, our study shows that autophagy dysfunction contributes to iron-induced α-synuclein pathology.